Visualization of the Redox Status of Cytosolic Glutathione Using the Organelle- and Cytoskeleton-Targeted Redox Sensors - Yuta Hatori; Takanori Kubo; Yuichiro Sato; Sachiye Inouye; Reiko Akagi; Toshio Seyama (MDPI AG, 2020)
Glutathione is a small thiol-containing peptide that plays a central role in maintaining cellular redox homeostasis. Glutathione serves as a physiologic redox buffer by providing thiol electrons for catabolizing harmful oxidants and reversing oxidative effects on biomolecules. Recent evidence suggests that the balance of reduced and oxidized glutathione (GSH/GSSG) defines the redox states of Cys residues in proteins and fine-tunes their stabilities and functions. To elucidate the redox balance of cellular glutathione at subcellular resolution, a number of redox-sensitive green fluorescent protein (roGFP) variants have been developed. In this study, we constructed and functionally validated organelle- and cytoskeleton-targeted roGFP and elucidated the redox status of the cytosolic glutathione at a subcellular resolution. These new redox sensors firmly established a highly reduced redox equilibrium of cytosolic glutathione, wherein significant deviation was observed among cells. By targeting the sensor to the cytosolic and lumen sides of the Golgi membrane, we identified a prominent redox gradient across the biological membrane at the Golgi body. The results demonstrated that organelle- and cytoskeleton-targeted sensors enable the assessment of glutathione oxidation near the cytosolic surfaces of different organelle membranes.